A general design strategy for thermoelectric interface materials in n-type Mg3Sb1.5Bi0.5 single leg used in TEGs. (March 2022) - Wu, Xinzhi; Han, Zhijia; Zhu, Yongbin; Deng, Biao; Zhu, Kang; Liu, Chengyan; Jiang, Feng; Liu, Weishu
Abstract: The reliability of thermoelectric power generators (TEGs) depends heavily on the contact interface between thermoelectric (TE) materials and electrodes. We propose a general alloying approach for generating TE interface materials (TEiMs) for n-type Mg3 Sb1.5 Bi0.5 systems. The TEiM serves as a metallisation layer or barrier that precedes the soldering assembly. We first selected Fe from 15 elements as the matrix element considering the criteria of high bonding strength and low interfacial resistivity. Following the principles of high bonding propensity, coefficient of thermal expansion (CTE) matching, diffusion passivation, and dopant inactivation, two types of ternary alloys (Fe7 Mg2 Cr and Fe7 Mg2 Ti) with shear strengths ( σ s ) of > 40 MPa and the specific contact resistivities ( ρ c ) of < 5 µΩ cm 2 were obtained. Furthermore, the thermal stability of the TEiM/Mg3 Sb1.5 Bi0.5 contact interface was investigated employing aging treatment. The contact interface exhibited high shear strength ( σ s > 30 MPa ), low specific contact resistivity ( ρ c < 10 μ Ω c m 2 ), and excellent thermal stability after aging treatment at 400 °C for 15 days. The general TEiM design strategy presented herein will contribute to further optimization of contact interfaces in TEG devices. Graphical abstract: Image, graphical abstract